Economic analysis of forest insect pests in Canada. (19th June 2015) - Niquidet, Kurt; Tang, Jingwen; Peter, Brian
Abstract: Canada is host to a number of native and introduced forest insects that negatively affect the goods and services provided by forests. Some insects affect forests on a fairly predictable, ongoing basis, while others have impacts that are intermittent, difficult to predict, and sometimes catastrophic. Economic analysis has provided important insights that have informed our understanding of the impact of forest pests and pest management. At the same time, interactions between forests, forest insects, forest management, and economic welfare are complex, and credible assessments may be time consuming and may not always provide results with the certainty sought by policy-makers. This paper reviews the contribution of economics to forest pest management in Canada and suggests future directions for this important field of research.